Enterobiasis en la población de 5 a 11 años de los colegios del distrito de Quisqui-Huánuco - Espinoza Livias, Franco Elio (2018)
Introduction: The objective of the present study was to determine the frequency and factors related to enterobiasis in the population from 5to 11 years of Quisqui-Huanuco district schools during the period from June to September of 2014. Methods: A prevalence study wasconducted in 430 children, taken randomly from 880 children aged 5 to 11 years (CI: 95%). All data was collected from primary sources:interview and report on results of the test of Graham. The collection of the samples for the diagnosis of Enterobiasis was serial, by Grahamtechnique, for 3 consecutive days, which were then analyzed by direct microscopy. Results: Found an overall prevalence of Enterobiasis of60%. The differences between the frequencies of infection according to age and sex were not significant. Showed a greater percentage offemale infection which in the male (63.5% vs. 56.8%), and in the age range > 8 years. In bivariate analysis it was found significant Association(P< 0,05) with the educational level of mother, health hygiene, overcrowding, sewage disposal, source of water, onicofagia and wormingprior. The 85.1% of the children had symptoms, abdominal pain, anal itching, and the decreased appetite being the most common symptomswith 71.6%, 49.1% and 48.1% respectively. Conclusions: The high prevalence reflects a direct relationship with the unfavourable socioepidemiologicalconditions, which would facilitate the continuous processes of infection.